Regulation of microRNA biogenesis and function - Treiber, Thomas; Treiber, Nora; Meister, Gunter (Thrombosis and Haemostasis, 2012)
MicroRNAs (miRNAs) are considered as key regulators of literally all cellular pathways. Therefore, miRNA biosynthesis and their individual cellular functions must be tightly regulated as well. MiRNAs are transcribed as primary transcripts, which are processed to mature miRNAs in two consecutive maturation steps. Finally, the mature miRNA is incorporated into a miRNA-protein complex, where it directly interacts with a member of the Argonaute (Ago) protein family. The miRNA guides such protein complexes to partial complementary target sites, which are typically located in the 3’ untranslated region (UTR) of mRNAs leading to inhibition of gene expression. MiRNA activity and abundance is regulated on various levels ranging from transcription and processing to target site binding and miRNA stability. Recent advances in our understanding of how miRNA activity is regulated in mammalian cells are summarised and discussed in this review article.
Keywords: microRNAs; Dicer; Drosha; Argonaute; gene silencing